Perencanaan Gedung Sekolah Inklusif SD Islam Al Madani Banjarbaru - Muslim, Royadin (Lambung Mangkurat University Press, 2023)
Al Madani Islamic Elementary School needs an inclusive school building that is friendly to persons with disabilities. For this reason, technical planning by a planning consultant is needed as a reference for the implementation of the construction. Through the planning process a building technical design document is produced consisting of technical drawings, technical specifications, general specifications, volume/quantity and budget plan. This document is needed as a reference for construction costs, to fulfill the requirements of the Government's Building Approval, and as a reference in the implementation of building construction.